Ab Initio Calculation of Li-Sn System: Unraveling New Phases of Superconducting Materials with Increasing Compression - Thong, Leng Lim; Tiem, Leong Yoon; Yee, Hui Robin Chang; San, Kiong Lai (Penerbit UiTM, 2021)
Stoichiometry, crystal compound, electronic attributes and superconductivity of compressed lithium-tin composites have been thoroughly studied using quantum mechanical genetic algorithm approach and the first principles computations based on density functional theory. Our simulations at moderate pressure (5-20 GPa) predict a complex convex hull diagram, with the following stable Li-rich phases: I4/mmm-Li6Sn2, P3m1-Li7Sn2, R3m-Li5Sn2, Ama2-Li4Sn2, R3m-Li5Sn2, P1-Li6Sn2, C2/m-Li4Sn1, P21/m-Li6Sn2, P3m1-Li7Sn2 and Cmcm-Li4Sn2. Careful examination at their independent elastic parameters reveals sufficient mechanical stability in them. These phases are metallic system, with reasonably high electron concentration near to Fermi level or N(EF) that ranges from 0.6 to 2.4 states/eV cell. It is also interesting for us to observe soft modes and steep-flat energy bands at Fermi levels of Li6Sn2 structures which are stable throughout the pressure range. These features are prerequisites for superconducting behavior. Linear response function with Gaussian and tetrahedron methods reveals satisfactory superconducting transition temperature Tc (3.1 ~ 6.6 K) and Tc (2.1 ~ 2.4 K), respectively. Structural transition results for based elements Li and Sn agree well with literature thus signifying reliable prediction of intermediate phases.